(untitled) (Global Journal of Human-Social Science, 2015)
The main objective of this transversal study was to examine the relation of morphological and conative characteristics (normal and pathologic) factors in volleyball junior players. The data were collected on the sample of examinees (N = 126), aged 16 to 17 years from five volleyball clubs. The applied measuring instruments consisted of 23 anthropometric measures, 16 normal and 12 pathological conative variables. Descriptive statistics, Pearson’s correlation coefficient and canonical correlation analysis were applied for data processing. The results showed that among the set of anthropometric characteristics and set of normal conative dimensions, with 51% of explained variance, there is a statistically significant canonical correlation of high level (Rc =.77, p < .05), whereas among the set of normal and pathological conative dimensions, with the interpreted variability of 59%, two significant correlations of average intensity (Rc = 73, p < .01, and Rc = .70, p